Evaluation of Cloud-Based Ethereum Network Performance - Sundara, Tri; Arief, Lathifah (The Indonesian Journal of Computer Science, 2022)
Ethereum, that enable development of decentralized applications, will likely to leverage cloud computing. In this research, we evaluate the performance of a cloud-based Ethereum network. We researched 3 Ethereum networks, namely: Ethereum mainnet, Ethereum testnet Ropsten, and Ethereum testnet Rinkeby. We analyze the computational resource utilization required to run an Ethereum node for a month as well as the costs involved. Research shows that the utilization of computing resources on the Main Net is generally higher than on the Test Net network. Computing resources used in the cloud cost thousands of dollars and this will increase as the number of nodes running to support the Ethereum network.